PENGARUH MEDIA SOSIALISASI LINGKUNGAN TERHADAP KESADARAN MASYARAKAT DI WONOCOLO KOTA SURABAYA DALAM PENGELOLAAN SAMPAH - Amanda Rizki Anindya; Chamela Neo Farega; Dini Revina Septyaningsih (Jurnal Dialektika Politik, 2026)
This research aims to examine the impact of social media content focused on environmental issues on the extent of public understanding regarding waste management initiatives within the Wonocolo Subdistrict, Surabaya City. A quantitative approach with an analytical survey design was applied, using probability random sampling involving 65 respondents, Data acquisition was performed using closed-ended survey instruments that underwent rigorous validation and reliability assessments. The analytical procedures encompassed validity and reliability evaluations, classical assumption testing, simple linear regression analysis, F-tests, t-tests, and the computation of the coefficient of determination (R²). The findings suggest that environmental communication platforms exhibit a substantial impact on public awareness of waste management, as shown by the observed t-statistic value of 6.011 exceeding the critical value of 1.99962 and statistical significance of 0.000, a value less than the predetermined threshold of 0.05. Consequently, the null hypothesis (H₀) was rejected in favor of the alternative hypothesis (H₁). The coefficient of determination (R²) was found to be 36.5%, indicating that indicates the ability of socialization media to explain changes in public awareness levels, while the remaining 63.5% is attributable to other external factors. The regression model obtained was Y = 19.254 + 0.514X, indicating that every one-unit increase in the environmental socialization media variable is associated with an increase of 0.514 units in public awareness, thereby showing that socialization through face-to-face meetings and digital media has a substantial impact on promoting public awareness of cleanliness and waste management.